SDN-supported edge-cloud interplay for next generation internet of things - Sahoo, Kshira Sagar; Solanki, Arun, 1985-; Mishra, Sambit Kumar; Sahoo, Bibhudatta, 1967-; Nayyar, Anand (Boca Raton : Chapman & Hall/CRC Press, 2023)
"SDN-Supported Edge-Cloud Interplay for Next Generation Internet of Things is an invaluable resource which provides a wide range of research directions in the field of edge-cloud computing, SDN, and IoT. The integration of SDN in edge-cloud interplay is a promising framework for enhancing the QoS for complex IoT-driven applications. Interplay between cloud and edge solves major challenges arises in traditional IoT architecture. This book is a starting point for those involved in this research domain and explore different burning issues related to network congestion, traffic management, latency, QoS, scalability, security, and controller placement problems etc"--
SDN based IoT with edge computing / Sreenivasa Rao Annaluri, Venkata Ramana Attili & Mohan D -- Towards cloud-edge-of-things : state-of-the-art, challenges and future trends / Lopamudra Hota & Prasant Kumar Dash -- Edge AI : A broad view in real time / Joshila Grace.L.K, S. Jancy, A.C. Santha Sheela, L.Sujihelen & G.Nagarajan -- SDN aided edge computing enabled AI for IoT and smart cities / Rashandeep Singh, Sunil Kr. Singh, Shabeg Singh Gill & Sudhakar Kumar -- An overview of software defined internet of vehicles / Sagarika Mohanty, Bibhudatta Sahoo, Hemant Kumar Apat & Kshira Sagar Sahoo -- IoT architecture and research issues in smart city environment / Shreeya Swagatika Sahoo, Asit Sahoo & Bibhudatta Sahoo -- Performance evaluation methods for SDN controllers : a comparative analysis / Jehad Ali, Byeong-hee Roh & Sahib Khan -- A scalable software defined edge computing model for sustainable smart city internet of things (IoT) application / Hemant Kumar Apat, Bibhudatta Sahoo, Sagarika Mohanty & Kshira Sagar Sahoo -- Deep learning models with SDN and IoT for intelligent healthcare / Vedaant Singh & Srishty Singh -- Internet of drones application in aircraft MRO business services / Ms. Bharati Singh & Saurabh Tiwari -- Applications of machine learning techniques in SD- IoT traffic management / Anchal, Pooja Mittal, Preeti Gulia & Balkishan.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Software-defined networking (Computer network technology); Edge computing; COMPUTERS / Machine Theory; COMPUTERS / Artificial Intelligence